PENGGUNAAN THREE-TIER TEST UNTUK MENGUNGKAP HAMBATAN EPISTEMOLOGI DALAM MATERI SPLDV - Kurnia Yunita; Sugiatno Sugiatno; Dede Suratman (UNIVERSITAS TANJUNGPURA, 2020)
This research is aimed to describe the epistemology obstacle using the three-tier test in SMP Muhammadiyah 2 Pontianak. The method that used in this research is qualitative descriptive with the form of a survey. The subject is 33 students from grade 9 of SMP Muhammadiyah Pontianak academic year 2019/2020. The result from this research showed that the three-tier test instrument can reveal students epistemology obstacles based on the indicator. Conceptual obstacle could reveal that students still lacking in constructing mathematics models. It happened because students still make mistakes in presupposing and confuse in reasoning. The procedural obstacle could reveal that incompatibility in question completion steps and the inability to complete the question in a very simple form. It happened because the students working process is different from the direction in the question, students are not able to complete and do the questions. The technical operational obstacle could reveal that errors in calculating numbers from the sum of integers operation and errors in variable writing, writing incomplete steps and errors in switching the constants or the variables from previous steps.Keywords: Three-tier Test, epistemology obstacle, SPLDV